(untitled) (The Review of Diabetic Studies, 2025)
Evidence-based practice (EBP) has become fundamental to modern nursing, particularly in critical care settings where clinical decisions directly impact patient survival and recovery. This paper examines the implementation of EBP in critical care nursing and its effects on patient outcomes. Through comprehensive analysis of recent literature, this review explores the theoretical foundations of EBP, barriers to adoption, strategies for successful implementation, and measurable improvements in patient care quality across multiple domains. The findings demonstrate that systematic integration of EBP in critical care units significantly reduces complications, decreases length of stay, improves patient satisfaction, reduces healthcare costs, and enhances nursing professional development and job satisfaction. This paper also addresses the role of organizational culture, leadership, education, and technological innovations in facilitating EBP adoption. Recommendations for practice, policy, and future research are provided to advance the field and optimize patient care in critical care environments.